Physical, chemical, and mineralogical properties of agromarine waste ash - Obinna O. Barah; Milon S. Dennison; Stephen N. Nnamchi; Kennedy C. Onyelowe; Emmanuel B. O. Olotu (Discover Materials)
Abstract Agro-marine waste presents environmental challenges, demanding sustainable solutions. This study explores the potential of ashes from periwinkle shells, plantain stems, and eucalyptus wood for sustainable material use. Physical analyses reveal Periwinkle Shell Powder (PSP) with the highest bulk density (0.52–1.24 g/cm3) and specific gravity (2.05), ideal for load-bearing applications. Plantain Stem Ash (PSA) has a bulk density of 0.98 g/cm3 and fine particle sizes (< 45 µm), enhancing its pozzolanic activity for cementitious uses. Eucalyptus Wood Ash (EWA) shows a lower bulk density (0.2–1.0 g/cm3), suitable for lightweight applications like thermal insulation. Specific gravities are 2.62 (EWA), 2.67 (PSA), and 2.69 (PSP). Chemical analysis via X-ray fluorescence (XRF) identifies calcium oxide (CaO), silica (SiO₂), and potassium oxide (K₂O) as predominant oxides, driving pozzolanic reactivity. Trace amounts of magnesium oxide (MgO), aluminum oxide (Al₂O₃), and iron oxide (Fe₂O₃) enhance structural stability. PSA’s low moisture content (< 5%) ensures superior reactivity, while EWA’s slightly higher moisture (~ 1%) remains viable for low-moisture environments. Microstructural analysis using scanning electron microscopy (SEM) reveals porous, irregular surfaces, improving adsorption and bonding. Energy-dispersive X-ray spectroscopy (EDS) confirms agglomerated particles and fine crystalline phases, supporting industrial use. These findings highlight agro-marine waste ash as a sustainable alternative for applications like supplementary cementitious materials, fillers, and adsorptive agents, offering a pathway for waste valorization and environmental sustainability.